ADVANTAGES OF SCHOOL EDUCATION OF MATH USING DUAL PROBLEMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article explores the concept of dualism, the concept of duality in geometry and algebra. The advantages of using dual tasks in teaching mathematics in school mathematics on specific tasks are highlighted and demonstrated.